Usage of Shanghai Scoring System for Predicting Ventricular Arrhythmic Events in Brugada Syndrome (BrS) Patients in Thailand - Chintanavilas, Kumpol; Methachittiphan, Nilubon; Apiyasawat, Sirin (Asian Medical Journal and Alternative Medicine, 2023)
Background: Many risk factors are associated with ventricular arrhythmic events in Brugada syndrome (BrS) patients. The Shanghai scoring system for diagnosis of BrS was initially published in 2015.1 A single study also validated using this scoring system for risk stratification of arrhythmic events in BrS patients.2 There has been no study to demonstrate the role of this scoring system in the risk stratification of BrS patients in the Thai population. This study aimed to evaluate the role of the Shanghai scoring system in predicting ventricular arrhythmic events in Thai BrS patients. Method: We studied a retrospective cohort of BrS patients who were diagnosed from 1999 to 2019 at Ramathibodi Hospital. The patients were classified according to the Shanghai scoring system. All patients were followed for arrhythmic events and clinical outcomes. Result: 54 Patients (14 with cardiac arrest, 30 with syncope, 3 agonal respirations, and 7 asymptomatic) were classified by the Shanghai score into group A (Very high risk); score ≥ 5.5 (n=34), group B (High risk); score 4-5 (n=14) and group C (Non-high risk); score ≤ 3.5 (n=6). During the follow-up period of 114 months, 11 arrhythmic events occurred (1 sudden cardiac arrest, 9 appropriate ICD therapy, 1 documented VT/VF from surface ECG). Incidence of ventricular arrhythmic events was highest in Group A (26.5%), followed by Group B (14.3%), and no event in Group C. Shanghai scores of more than 3.5 tend to be associated with increased ventricular arrhythmic events (HR 4.85, CI 0.037-630.2, p=0.525), compared to the lower risk group (Shanghai score ≤ 3.5). Five inappropriate ICD shocks occurred. Device-related complications occurred in 8 patients, with lead fracture being the most frequent complication (9.3%). Conclusion: Risk stratification by the Shanghai scoring system may be useful in predicting ventricular arrhythmic events in Thai BrS patients. However, a larger cohort is needed for statistically significant results.